The Impact of Leadership, Work Motivation and Work Environment on Employee Performance at XYZ Resto - Rijal Asy'ari, Muhammad; Indiyati, Dian (International Journal of Science, Technology & Management, 2024)
This study aims to analyze leadership, work motivation, work environment and employee performance at XYZ Resto; to analyze the influence of leadership, work motivation and employee work environment on employee performance. This study uses quantitative methods with a descriptive and verification approach. Data collection techniques are carried out by distributing questionnaires, which must be tested for validity and reliability. The population in this study were employees at all XYZ Resto branches, totaling 250 people, where the sample was taken as much as 40% to 100 people. This study uses path analysis as a data analysis tool. The hypothesis is that leadership, work motivation and work environment have a significant effect on employee performance at XYZ Resto. Based on the research findings, it was found that the influence of the three variables of Leadership, Motivation and Work Environment simultaneously on the Employee Performance variable is 62.5%. While 37.5% is influenced by other variables outside those studied.